PEMIKIRAN POSTMODERNISME DAN PANDANGANNYA TERHADAP ILMU PENGETAHUAN - Johan Setiawan; Ajat Sudrajat (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
The birth of postmodernism can not be separated from the notion of modernism. The view of modernism assumes that the truth of science is absolute and objective, meaning that there is no human value. Here is the birth of a new idea of postmodernism which is one of figures are Jean Francouis Lyotard, postmodernism is a continuation and correction of modernism to provide a new thought and solution in his view of science. For postmodernism, science is not objective but subjective and the interpretation of man himself, so the truth is relative. Postmodernism can not be separated by its weakness and whether it is relevant to today’s life, so postmodernism adds to the acquisition of knowledge which can be accepted by its existence.